Implications of substrate geometry and coating thickness on the cracking resistance of polymer-based protective coatings - Wray, Lesley-Anne; Ayre, David; Irving, Phil E.; Jackson, Paul A.; Jones, P. R.; Zhao, F. (Elsevier, 2018)
Welded steel T-sections of different weld fillet geometries coated with water ballast tank protective coatings were subjected to thermal cycling with a temperature range from 60°C to -10°C. Cracks developed in the coatings at the weld line, propagating longitudinally along it. The number of cycles required to create 1 mm cracks was strongly dependent on the weld geometry and the coating Dry Film Thickness (DFT). Finite Element Modelling (FEM) was employed to calculate thermally induced strain fields in the coatings subjected to the same temperature range. FEM predicted that the greatest strain concentrations are present at the coating surface within the weld fillet region. Increased DFT and decreased fillet radius leads to increased maximum principal strains. Numerical analysis predicts that greatest strain ranges promoting the earliest cracking/failure are found in thicker coatings applied to smaller weld radii. Experimental observations confirm this.
Keywords: Coatings; Thermal Strains; Fatigue; FEM Analysis; Cracking Failure; Coating Life